From intention to perception: emotional processes as a link between intended and perceived leadership styles - Mindeguia, Rosa; Aritzeta, Aitor; Garmendia, Alaine; Olarza, Amaiur (Frontiers in Psychology, 2025)
IntroductionResearch has shown that managers and employees often differ in their perceptions of leadership, and that agreement between them is essential for effective leadership. Leadership involves both the actions of leaders and the perceptions of followers who interpret those actions within organizational contexts. Thus, the extent to which intended leadership styles influence followers—and, consequently, organizations—may depend largely on followers’ perceptions. It is therefore important to analyze the relationship between leaders’ intended leadership styles, followers’ perceptions of leadership, and the mediation processes between them. This study explored the mediating effects of management team emotional intelligence (TEI), the discrete emotions of followers and work units, and their roles in linking intended and perceived leadership styles.MethodsData were collected from two sources: 1,566 managers organized into 188 teams, and 4,564 workers. Multilevel path analysis was used to examine the relationships among variables.ResultsThe findings showed that TEI and employees’ emotional states fully mediated the relationship between management teams’ intended transformational leadership and employees’ perceived transformational leadership.DiscussionThis study highlights the central role of emotional processes in leadership effectiveness. TEI in management teams enhances the impact of intended transformational leadership (TFL) by shaping followers’ emotional states and perceptions. Positive, high-intensity emotions strengthen perceptions of leadership, whereas low-intensity states, such as comfort, weaken them. These findings advance our understanding of how leaders’ emotional skills and group affect contribute to creating more transformational leadership processes.